The persistence-resilience trade-off in unemployment: The role of labor and product market institutions - Tolga Aksoy; Paolo Manasse (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2018)
The "great recession" has affected labor markets in Euro-area countries in very different ways. This chapter documents two important aspects of their response: the impact effect of the recession on the rate of unemployment, and the persistence of high unemployment. We find that countries lie on a trade-off between "resilience" and "persistence": countries where the rate of unemployment is less affected on impact by output shocks (resilience) typically show higher unemployment persistence. We investigate the role of labor and product market institutions, and find evidence that more protected markets are associated to more resilience at the expense of more persistence. This suggests that implementing front loaded "structural reforms" at times of a fiscal consolidation, as many Southern European countries did during the recent crisis, may foster the rise in unemployment and possibly undermine the political support for the reforms. When we estimate the contribution of product and labor market reforms to the rise of unemployment in Southern Europe, however, we find positive, but relatively small effects that are quickly reversed.
Keywords: E02; E65; 330; Structural Reforms; Economic Crisis; Banking Crisis; Labor Market Reforms; Product Market Reforms; Banking Sector Reforms